No cold feet in a COVID-19 world – Disruptions and opportunities - WONG, James (Institutional Knowledge at Singapore Management University, 2020)
Join the instructional librarians from NIE as they share their journey to change how information literacy and research skills programs are delivered due to COVID-19 disruptions. Walk with them as they share their struggles, victories, and aspirations in this ongoing transformative journey to offer new library interventions to faculty and students.